Social emotional learning (SEL) matters: differences in student perceptions of SEL before and during COVID-19 - Wetzel, Cassandra (Kansas State University, 2022)
The month of March 2020 is one that will not be forgotten. The coronavirus disease (COVID-19) is caused by a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the outbreak forced schools to close their doors and quickly develop a virtual learning platform where students would be learning virtually in their homes. Social-emotional learning (SEL) has always been important but it has been emphasized even more so throughout the pandemic. Numerous studies over the years have emphasized the importance of SEL for students’ education and development as it influences achievement and long-term outcomes. This quantitative study investigated the differences among student SEL, measured by Panorama Education’s SEL student perception data from students in grades 3-12 and the COVID-19 pandemic. The researcher examined the data from Fall 2019, Fall 2020, and Fall 2021 to reflect differences in students’ SEL prior to the COVID-19 pandemic and during the pandemic. The researcher also examined the differences among student SEL results related to grade level during Fall 2019, Fall 2020, and Fall 2021.
Keywords: Social emotional learning (SEL); COVID-19; Panorama Education; Quantitative